Ta - Faris Maturedy; Primasti Nur Yusrin Hidayanti; Hauli Haikal (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2020)
Ma'had al Jami'ah students come from various educational backgrounds. Therefore, they have constraints in making Arabic conversation videos when they have college assignments. This study aims to describe the activities of conversation in Arabic in Ma'had al Jami'ah IAIN Jember. This research study uses a descriptive qualitative approach. Data were obtained from participant observation, interviews and documentation. Data analysis used the Miles & Huberman model analysis. The results of this study indicated that the Arabic language conversation activities consist of 3 activities. Namely, opening activities, core activities and strengthening activities. In the opening activity, the teacher provided questions and answers regarding the materials that have been studied. In the core activities, the teacher uses several methods, namely the direct method, the audio visual method and the qawaid wa tarjamah method. In the closing activity, the teacher provides material reinforcement and several language games. This research study is expected to provide a glimpse of the importance of active Arabic learning for the management of ma'had al Jami'ah IAIN Jember. so that it can improve the Arabic language learning program for mahasantri ma'had al Jamiah.